2008
DOI: 10.4088/jcp.v69n0310
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Acute Electroconvulsive Therapy in Atypical Depression

Abstract: Objective-This study examined the characteristics and outcomes of patients with major depressive disorder (MDD), with or without atypical features, who were treated with acute bilateral electroconvulsive therapy (ECT).Method-Analyses were conducted with 489 patients who met DSM-IV criteria for MDD. Subjects were identified as typical or atypical on the basis of the Structured Clinical Interview for DSM-IV obtained at baseline prior to ECT. Depression symptom severity was measured by the 24-item Hamilton Rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 38 publications
0
12
0
2
Order By: Relevance
“…Earlier onset of antidepressant response induced by ECT was also shown to correlate with better long-term outcome [68]. In a cohort of 253 depressed patients receiving ECT three times a week, Husain and colleagues observed that more than 50% achieved response within the first week, and 83.4% responded within two weeks [69]. This same study also described a sustained response in 34.8% of patients during the first week and in 64.4% within the second week (at or before their sixth session of ECT); 34% experienced remission before or at the end of Week 2.…”
Section: Pharmacological and Non-pharmacological Approaches And Thmentioning
confidence: 99%
“…Earlier onset of antidepressant response induced by ECT was also shown to correlate with better long-term outcome [68]. In a cohort of 253 depressed patients receiving ECT three times a week, Husain and colleagues observed that more than 50% achieved response within the first week, and 83.4% responded within two weeks [69]. This same study also described a sustained response in 34.8% of patients during the first week and in 64.4% within the second week (at or before their sixth session of ECT); 34% experienced remission before or at the end of Week 2.…”
Section: Pharmacological and Non-pharmacological Approaches And Thmentioning
confidence: 99%
“…A survey of recent clinical trials in ECT uniformly showed that a diagnosis of dementia was a criterion for exclusion from study participation. 17-19 This raises the question of how to operationalize the identification of dementia. In addition to a pre-existing clinical diagnosis of dementia, a possible diagnosis of dementia may be based upon a pre-defined cut-off score on a neuropsychologic instrument such as the Mini Mental State Examination (MMSE) 20 or the second edition of the Dementia Rating Scale (DRS-2).…”
Section: Case Presenstationmentioning
confidence: 99%
“…[17][18][19] Data from the multicentre study by the Consortium for Research in Electroconvulsive Therapy suggest that the median number of electroconvulsive therapy treatments required to produce an antidepressant response is 3, the number for resolution of suicidal thoughts is 4, and the number for remission is 7.…”
Section: Electroconvulsive Therapymentioning
confidence: 99%